Tree species composition and height structure of undergrowth in fresh hornbeam-oak-pine forest on relatively rich soils of the Ukrainian Roztochia - Lavnyy, V.V.; Kravchuk, R.M.; Vytseha, R.R.; Spathelf, P. (Forestry, Forest, Paper and Woodworking Industry, 2021)
The fresh hornbeam-oak-pine forest on relatively rich soils of the Ukrainian Roztochia is characterized by a good natural regeneration of tree species, both under the forest canopy after the first irregular shelterwood cutting, and on two clear cut areas. After the first irregular shelterwood cutting, the total amount of self-seeding and undergrowth changes from unsatisfactory (10.480 pieces/ha) at the beginning of the 2020 vegetation season to good (41.528 pieces/ha) at the end of the 2020 growing season. A year later, its number has not changed and 42.693 individuals/ha were counted. However, the share of pedunculate oak in the total number of undergrowth here is only 1.7%. Natural regeneration of all tree species under the forest canopy is characterized by an uneven distribution in the area. Hornbeam has the highest incidence rate - 75.6%. Species such as Scots pine, hanging birch and goat willow have a frequency of 30.8 to 39.7%. Other tree species are much less common, including pedunculate oak (abundance from 1.3% to 12.8%). On clear cut areas the total amount of self-seeding and undergrowth varies from 175.6-275.3 units/ha at the beginning of the vegetation period of 2020 to 299.4 thousand pieces/ha at the end of that vegetation period, and a year later, in autumn 2021 it reached 461.2 thousand pieces/ha. Hornbeam also had the highest abundance rate - 97.3-98.1%, followed by pedunculate oak (43.5-77.3%), birch (42.6-52.7%) and pine (29.6-34.0%). Other tree species, such as lime, willow, sycamore, beech, elm, aspen, and others, had a frequency of 0.7 to 20%. In general, in all the studied areas, the composition of self-seeding and undergrowth was dominated by a small fraction up to 20 cm in height. To ensure the advantage of pedunculate oak in the naturally formed young stands in all areas it is necessary to carry out silvicultural treatments such as cleaning or precommercial thinning.